Improving Islamic Religious Education Learning through the Method of Giving Learning Assignments and Recitations to Students at SD Negeri 100609 Hurase - Hidayat, Rahmat (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to determine the effect of implementing the method of giving learning assignments and recitations in improving the learning outcomes of Islamic Religious Education (PAI) in students at SD Negeri 100609 Hurase. The research method used is Classroom Action Research (CAR) with a cycle approach consisting of two cycles. Each cycle includes the stages of planning, implementing actions, observation, and reflection. The subjects of this study were 30 fifth grade students consisting of 15 male students and 15 female students. The results showed that the implementation of the method of giving learning assignments and recitations had a significant impact on improving PAI learning outcomes. The average score of students in the pre-test was 60%, while in the post-test after the second cycle it increased to 85%. In addition, there was a significant increase in student participation and involvement during the learning process. Initially, many students were passive, but after this method was implemented, almost all students actively participated in group discussions, completing assignments, and doing recitations. Improvement in recitation skills is also clearly visible, where students who were initially hesitant in reading the verses of the Qur'an and Hadith become more confident and fluent in doing so. In addition, students are also better able to apply Islamic moral values ​​in everyday life situations. Based on student feedback and teacher reflection, it can be concluded that this method has succeeded in creating a more interactive and collaborative learning environment. This study concludes that the method of giving learning assignments and recitation is effective in improving Islamic Religious Education learning outcomes, recitation skills, student participation, and students' ability to apply Islamic moral values. Therefore, it is recommended that this method be applied more widely in Islamic Religious Education learning to improve the quality of learning and moral development of students.